Long-Noncoding RNA MANCR is Associated With Head and Neck Squamous Cell Carcinoma Malignant Development and Immune Infiltration - Tang, Jianfei; Bao, Mingyan; Chen, Juan; Bin, Xin; Xu, Xinghuanyu; Fang, Xiaodan; Tang, Zhangui (Frontiers in Genetics, 2022)
Recent studies have demonstrated that an important role for MANCR in carcinogenesis and cancer progression, but its function has not been elucidated in HNSCC. In this study, we identify differentially expressed MANCR from The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) databases which across 24 cancer types and included 546 HNSCC patients. Further, high expression of MANCR was verified in HNSCC cell lines and tissue and by using real-time quantitative PCR (RT-qPCR) analysis. And Kaplan–Meier analysis shown a worse prognosis with higher levels of MANCR for HNSCC. The analysis of univariate Cox regression and multivariate Cox regression revealed that MANCR was a high-risk factor in patients with HNSCC. Thereafter, we carried out Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses. It was indicated that MANCR participates in axonogenesis and ECM-receptor interaction. Further enrichment analysis demonstrated the expression of MANCR was positively correlation with the T gamma delta (tgd) cells, neutrophils, Th1 cells and negatively correlated with the infiltration of B cells, CD8 T cells and T cells in HNSCC. Besides, in vitro experiments showed that knockdown of MANCR in HNSCC cells markedly inhibited cell proliferation, migration and invasion. We find that MANCR was elevated in HNSCC and promoted malignant progression of HNSCC. MANCR may serve as biomarker in prognostic implications for HNSCC patients. The positive correlation between MANCR and immune inﬁltration cells, which may provide novel therapeutic targets and personalized immune-based cancer therapy for HNSCC.